Izbrane prvine nejezikovnega konteksta umetnostnih in polumetnostnih besedil - Krajnc Ivič, Mira (Slavia Centralis, 2020)
SELECTED ELEMENTS OF THE NON-LINGUISTIC CONTEXT OF LITERARY AND SEMI LITERARY TEXTS Two types of revitalisation are present in semi-literary and especially in literary texts: in addition to Saussure’s dichotomy of signifier and signified, there exist the revitalisation of the elements of non-linguistic context, such as those of the physical, social and mental worlds and the manners of their textualisation. Knowledge of communicative principles and the strategic capability to choose between either the fulfilment or nonfulfillment of the cooperative and politeness principles are classified as elements of the mental world of the inner participants of the communicative event. Observation of the individual’s mental world can interfere with their privacy, which is also why semi-literary and literary texts are useful material that clearly shows how the elements of non-linguistic context affect the formation of meaning for any textual message.